1999
DOI: 10.1126/science.286.5448.2333
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the West Nile Virus Responsible for an Outbreak of Encephalitis in the Northeastern United States

Abstract: In late summer 1999, an outbreak of human encephalitis occurred in the northeastern United States that was concurrent with extensive mortality in crows (Corvus species) as well as the deaths of several exotic birds at a zoological park in the same area. Complete genome sequencing of a flavivirus isolated from the brain of a dead Chilean flamingo (Phoenicopterus chilensis), together with partial sequence analysis of envelope glycoprotein (E-glycoprotein) genes amplified from several other species including mosq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
1,009
2
18

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 1,458 publications
(1,061 citation statements)
references
References 15 publications
17
1,009
2
18
Order By: Relevance
“…This high degree of sequence identity between US and Israel WNV strains support the hypothesis that the US WNV strains originated from the Middle East [7]. …”
Section: The Virus and Its Genomesupporting
confidence: 64%
See 4 more Smart Citations
“…This high degree of sequence identity between US and Israel WNV strains support the hypothesis that the US WNV strains originated from the Middle East [7]. …”
Section: The Virus and Its Genomesupporting
confidence: 64%
“…Studies of the phylogenetic relatedness on nucleic acid sequence data corresponding to a 255-bp region of the E glycoprotein gene of WNV strains isolated in different geographic regions, demonstrated that WNV isolates fall into two major genetic lineages diverging by 25 to 30% nucleotide differences [12, 13] and several subclades or clusters [7, 12, 14-16]. Lineage 1 is composed of WNV strains with a broad geographical distribution ranging from West Africa to the Middle East, Eastern Europe, North America, and Australia.…”
Section: The Virus and Its Genomementioning
confidence: 99%
See 3 more Smart Citations